2012
DOI: 10.7182/pit2012612
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Infection Control Measures for the Percutaneous Lead among Programs Implanting Long-Term Ventricular Assist Devices in the United States

Abstract: Ventricular assist devices (VADs) are a surgical treatment for heart failure. These devices may be implanted as a bridge to transplant or as destination therapy. After surgical recovery and education regarding device care, patients are discharged home. Meticulous care of the driveline must be taken to prevent infection and trauma of the site throughout the perioperative event and for the duration of support. Currently a standardized protocol for care of the driveline and exit site does not exist. VAD coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Despite all these issues and the fact that over 15,000 VADS have been implanted worldwide, (15) there is no consensus on the optimal driveline management protocol, as evidenced by a recent US survey of VAD centers. (7) Driveline management consists of driveline stabilization as well as the exit site cleansing and dressing. In this study, we demonstrated a significant decrease in DLI in our VAD population by a change in driveline management strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all these issues and the fact that over 15,000 VADS have been implanted worldwide, (15) there is no consensus on the optimal driveline management protocol, as evidenced by a recent US survey of VAD centers. (7) Driveline management consists of driveline stabilization as well as the exit site cleansing and dressing. In this study, we demonstrated a significant decrease in DLI in our VAD population by a change in driveline management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Several recent papers discuss alternative stabilization techniques for the driveline such as use of StatLock system with a silicone suture, Centurion Foley anchor, or Hollister tube holder instead of the abdominal binder that is easier and more comfortable for the patient to use. (7,8) The same survey also noted that there was no standard for dressing change protocols in terms of agents used and the frequency of dressing changes though 60% of programs reported daily dressing changes. It is also not clear if sterile technique should be applied at each dressing change.…”
Section: Introductionmentioning
confidence: 99%
“…7 Selection of products is based on prior experience or clinical preference with minimal guidance in the literature in terms of standardization. 8 Individualization results in variability in care in both the inpatient and outpatient setting, which can have a negative impact on patient compliance and increase the chances for infection. 5…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite efforts to provide education regarding dressing change procedures and supplies as part of the discharge process, 9 standardized techniques for dressing changes among VAD centers do not exist in the United States. 8 Survey results on outpatient management of adult patients with a continuous-flow VAD report a frequency in dressing changes ranging from once daily to once weekly. 10 Dressing change kits help to standardize and simplify driveline site management while providing added stability, promoting comfort, and decreasing the risk of infection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this study, it was possible to define a standard practice protocol based on the opinion of VAD specialists for general care of the equipment and patients. 25 Another complication associated with the use of this device is the occurrence of bleeding, which is caused by several factors such as coagulation disorders and hepatic dysfunction. 37 In addition, we can highlight complications including DNA damage and oxidative stress; 30 lower carotid artery complacency and distensibility, which can lead to pressure on the left ventricle; 29 multiple organ failure; neurological events 9 (long-term embolic or hemorrhagic events can occur); renal failure; 39 mechanical dysfunction; and psychological changes.…”
mentioning
confidence: 99%